Faktor-Faktor yang Berhubungan dengan Pengelolaan Obat Mandiri di Masyarakat Desa Tumbang Jutuh Kecamatan Rungan Kabupaten Gunung Mas Kalimantan Tengah - Patria Wana; Melviani Melviani; Dyah Sri Wahyuni (Jurnal Surya Medika (JSM), 2022)
Medicine management aims to ensure the availability of good quality medicine, in the right type, in the right amount, and at the right time and used rationally, therefore it is very important to know the factors related to medication management in the community in the village of Tumbang Jutuh if we know the factors we are can be modified for better management. This study aims to determine the relationship between information, education, and income with personal medicine management in the community. The type of this research is a quantitative research using a cross-sectional study design. The population and sample are people in the village of Tumbang Jutuh amount 102 people, the population in this research is included in the category of the infinite population. In this research, sampling refers to the Lemeshow sample measurement guidelines. The results based on the research, it was found that the influencing relation factors were information with personal medicines management, the p-value is 0.0001, and education with personal medicine management the p-value is 0.009. While the factor that does not affect is income with personal medicines management, the p-value is 0.192. Factors related to personal medicines management are information and education while income has no relationship.